Koncepcja narracyjnej oceny kapitału intelektualnego przedsiębiorstwa - Mroczko, Franciszek (The Concept of the Narrative Evaluation of a Company's Intellectual Capital, 2008)
The complexity of intellectual capital and its meaning for a company generate the need for the objective methods of evaluation and measurement. Unfortunately, all the previous theoretical achievements did not bring the solution to the problem. The author indicates that the narrative evaluation method may complement knowledge concerning the real state of a company's intellectual capital, especially its hidden values. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 235-243